A study on construction waste management (renovation work) / Muhammad Taufiq Ramlam - Ramlam, Muhammad Taufiq (Faculty of Architecture, Planning and Surveying, 2009)
Growth in construction activities generates construction waste which is fast becoming a serious environmental problem with deadly consequences. Most of the construction and demolition waste in our country are not recycled but end up in landfills occupying valuable land not to mention the cost incurred in landfilling. In line with this, a study on the benefits of waste minimization, the types and source of construction waste generation and methods used to dispose waste materials was carried out. The scope of study covers to person in-charge at renovation work site on construction waste management such as contractor, site supervisor or skilled worker. The area of this study is confined at Kuala Langat District Council (MDKL), Klang Municipal Council (MPK) and Shah Alam City Council (MBSA). The study was carried out by questionnaire and also an interview. A total of 16 respondents have submitted the completed questionnaire. Data was analyzed using average relative index. From the study, the benefits of waste minimization are conservation of natural resources, reduce environmental Impacts, increase profit, Increase landfill life and achieve a cleaner and safer construction site. The most frequent of waste material produced at construction site are cement plaster, steel, boards, timber, brick and paint barrel which causes by activities or factors of construction/renovation work, maintenance work, demolition work, design and material handling. The methods of waste disposal are landfill, dumping, open air burning, recycling and reuse.